What contributes to gendered work time inequality? An Australian case study? - Doan, Tinh; Thorning, Peter; Furuya-Kanamori, Luis; Strazdins, Lyndall (My University, 2021)
Women’s employment equality remains compromised by wage and work hour gaps, despite decades of policy action. Shorter work hours are a key to persisting disadvantage because they lock women out of high paying, good quality jobs. Such hour gaps are observed across all countries, and this paper quantifies the reasons behind them. We applied the Oaxaca decomposition method to a sample of employed adults from the Household Income and Labour Dynamics in Australia (HILDA). The method can show how the work hour gap would change if (a) women had the same sort of jobs (industry, occupation, work conditions, contract type) as men have and (b) if men lowered their work hours and/or increased their domestic unpaid work. We find that men’s allocation of time in and out of the home and the jobs women typically work in are central to explaining unequal paid hours. Women’s hours would increase (all else being equal) if they worked in the same industries and had the same job security as men have, accounting for 74% of the explained work hour difference. Women’s hours would also increase if they did the same (lower) domestic work as men, or if men worked the same (shorter) hours women typically do (33.4% of the explained gap). Our study, using Australian data, underscores the need to prioritize men’s time use (shorter paid hours, longer unpaid hours) alongside improvement in jobs and work conditions to progress gender equality in employment.
Social Indicators Research
Keywords: Families and relationships; Gender; Labour market